Primary duodenal malignant melanoma: A case report - Kazem Anvari; Masoumeh Gharib; Amir Hossein Jafarian; Amin Saburi; Seyed Alireza Javadinia (Babol University of Medical Sciences, 2018)
Background: Melanoma is a neoplasm derived commonly from melanocytic cells of skin. Although coetaneous presentation of malignant melanoma is easily recognizable, the presentation of melanoma in other organs is so confusing. In particular, when it metastasizes to other organs, many bizarre figures and unusual organs may be involved. In this report, we present a case of primary duodenal malignant melanoma. Case Presentation: A 68-year-old man presented with a history of iron deficiency anemia. The upper gastrointestinal endoscopy showed a prominent papilla of duodenum along with an ulcerative lesion adjacent to second part of duodenum. Histopathologic evaluation showed a high-grade malignant neoplasm involving the bowel wall which was labeled for S100 protein and markers of melanocytic differentiation; Melan-A indicating the definitive diagnosis of malignant melanoma of the second portion of duodenal mucosa. Conclusions: In patients with a history of iron deficiency anemia, any GI symptom should be evaluated carefully. However, the diagnosis of primary GI melanomas in patients without any history of melanoma is possible. Full medical investigations are recommended in these patients with primary mucosal lesions.